A kids book about perseverance - Lermer, Yonina Schnall (New York, NY : DK Publishing, 2025)
This is a kids' book about perseverance. In it, kids can learn to practice perseverance by learning the value of continued effort toward the things they love, even when it gets difficult. When we tell ourselves, "I can't do this," we give up. But when we say, "I can't do this yet," we're opening ourselves to the possibility of growing through challenges. So, let's add "yet" to our vocabulary and use it whenever we tackle new challenges!
K-3
Keywords: Perseverance (Ethics) -- Juvenile literature; Resilience (Personality trait) -- Juvenile literature; Conduct of life -- Juvenile literature; Perseverance; Resilience